Evaluation Of Rationality Of Antihypertension Drug Used at Pejagoan Community Health Center Period Of 2021 - Rafila Intiyani; Nabila Rizki Romadani; Tri Cahyani Widiastuti (Jurnal EduHealth, 2023)
The target population in this research were students of SMA Negeri 2 Bayang Pesisir Selatan who suffered from acne vulgaris on the facial skin. Data analysis using paired sample t test and independent t test. Result: most students are 17 years old 8 people (40%), the most gender are women as many as 18 people (90%), there is a effectiveness between the use of aloe vera facial wash and aloe vera gel with the degree of acne vulgaris in students at SMA Negeri 2 Bayang. (P = 0.000) and there is a effectiveness between the use of aloe vera facial wash and the degree of acne vulgaris in students at SMA Negeri 2 Bayang. (P=0.040). Conclusion: there is a the effectiveness application aloe vera facial wash and aloe vera gel between the degree of acne vulgaris in students at SMA Negeri 2 Bayang. Background, Hypertension or high blood pressure is a condition in which blood pressure increases to more than 140/90 mmHg. Based on the 2019 Kebumen District Health Profile, the total cases of hypertension patients at the Pejagoan Community Health Center in 2019 were 1,456 cases. There was an increase in the number of cases in 2020, which was 2,522 cases. The number of hypertension cases at Pejagoan Community Health Center is increasing every year, so the rational use of antihypertensive drugs is one of the important things to achieve health quality. The purpose of the study, the purpose of this study was to determine the rationality of the accuracy of drug use based on the right drug, the right dose, the right indication, and the right time interval in hypertensive patients at the Pejagoan Community Health Center in 2021. Research Methods, This research is a non - experimental observational conducted with descriptive method . The data collection method used retrospective data because the data was searched in the past from medical records using random sampling technique. The results of the study, the results showed that the rationality of the use of antihypertensive drugs at the Pejagoan Health Center in 2021 was the right drug 77.8%, the right dose 100%, the indication 100% right, the time interval 97.8%. Conclusion, Based on the results of this study indicate that the use of antihypertensive drugs at the Pejagoan Community Health Center is still not rational, because in its use there are still inappropriate drugs (22.2%) and inappropriate time intervals (2.2%). Recommendations, It is necessary to conduct further research on the evaluation of the use of antihypertensive drugs so that the treatment carried out on patients is more appropriate or rational